University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 9 - Section 9.9 - Convergence of Taylor Series - Exercises - Page 542: 22


$\Sigma_{n=0}^\infty (n+1)(n+2)x^{n}$

Work Step by Step

Since, we know that the Taylor Series for $\dfrac{1}{(1-x)^2}$ is defined as: $\dfrac{1}{(1-x)^2}=1+2x+3x^2+.....nx^{n-1}$ Now, $ (\dfrac{1}{(1-x)^2})'=[1+2x+3x^2+.....nx^{n-1}]'=2+6x+12x^2+....n(n+1)x^{n-1}$ $=\Sigma_{n=0}^\infty (n+1)(n+2)x^{n}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.